αβ T-cell development is not affected by inversion of TCRβ gene enhancer sequences: polar enhancement of gene expression regardless of enhancer orientation - Huang, Fang (Blackwell Science Inc, 2003)
V(D)J recombination and expression of the T-cell receptor β (TCRβ) gene are required for the development of the αβ T lymphocyte lineage. These processes depend on a transcriptional enhancer (Eβ) which acts preferentially on adjacent upstream sequences, and has little impact on the 5′ distal and 3′ proximal regions of the TCRβ locus. Using knock-in mice, we show that αβ T-cell differentiation and TCRβ gene recombination and expression are not sensitive to the orientation of Eβ sequences. We discuss the implication of these results regarding the mode of enhancer function at this locus during T lymphocyte development.